The future of the Tuttle Creek Reservoir project, Kansas - Archer, Jon (Kansas State University, 2003)
River fragmentation in the form of dams and reservoirs has changed the environment nationally. These reservoirs are only temporary, because sedimentation will cause many to become unusable by the middle of the twenty-first century. A number have become multi -resource facilities, and as such require holistic management. Despite the continued change of processes impacting dams and reservoirs, and uses of them, there is generally a lack of forward planning beyond the next five -to -ten years on the part of the federal and state organizations involved. This lack of planning leaves the far-reaching benefits, and populations used to the presence of the dams and reservoirs, as vulnerable, and recreational users under threat of losing a much -enjoyed resource. Using the case of the Tuttle Creek project in northeastern Kansas, this thesis investigates the background situation of big dam construction in the United States of America, including policies and changing perceptions. Investigating the dynamic factors impacting the project, including sedimentation, seismic activity, global climate change, recreational uses and wildlife habitation, alternative future uses are discussed. In this thesis, three possible futures are identified and evaluated, including removing the dam, reengineering it, and a no -action alternative. The U.S. Army Corps of Engineers and the Kansas Department of Wildlife and Parks are the major management organizations involved in the project. Successful execution of ensuing decisions for the future requires collaboration, something that could be difficult in the face of differing structures and management strategies.